Effects of Foliar Application Chitosan and Salicylic Acid on Physiological Characteristics and Yield under Deficit Irrigation Condition - Seyyed Ali Morovvat; Reza Sadrabadi; Koroush Shojaei Noferest; Alireza Souhani Darban; Mansour Salati (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
Drought stress is recognized as one of the most important factors reducing crop yields worldwide. Many studies are underway on the foliar application of different compounds to mitigate the effects of drought stress on plants. This experiment was designed to investigate the effects of foliar application of chitosan and salicylic acid on yield and its components under drought stress conditions in potatoes. The experimental design was split-plot with three replications based on a completely randomized design. The main plots and the sub-plots were 12 by 6 m and 6 by 3 m, respectively. The main plots represented three levels of irrigation (100%, 80%, and 60% of available soil water). Treatments in sub-plots included control treatment, 0.5 g/l salicylic acid, 2 g/l chitosan, and combined treatment with chitosan and salicylic acids. The results showed a direct relationship between reduced irrigation and reduced yield. As drought stress increased, yield, yield component parameters, and the physiological indices of the crop declined. Under stress conditions, the biological yield was increased by the application of chitosan and salicylic acid. The highest yield in non-stress conditions was 45,717 kg/ha; for foliar application of 0.5 g/l salicylic acid and 2 g/l chitosan, the highest yield was 45,683 kg/ha.